Sorption of Endocrine Disruptors onto Cell Membrane and the Effect of NOM - OGURI, Takuya; SHIMIZU, Yoshihisa; MATSUI, Saburo; IKEDA, Kazuhiro (ENVIRONMENTAL ENGINEERING RESEARCH, 2003)
The sorption coefficients (Kmw) of several endocrine disruptors {17β-estradiol (E2), 17α-ethynylestradiol (EE2), nonylphenol (NP), 4-(tert-octyl) phenol (OP)} onto cell membrane were measured using artificial cell membranes for evaluating their bioavailability and bioconcentration potential; and the effects of co-existing natural organic matter (NOM) on the sorption was evaluated. The Kmw of endocrine disruptors were comparable to that of 3-ring or 4-ring PAHs, which suggested that the specific interaction between membrane and endocrine disruptors greatly contributed to the sorption. The NOM itself was neither sorbed onto cell membrane nor affected the membrane fluidity. The co-existence of NOM reduced sorption of OP, NP and non-polar PAHs onto cell membranes. The co-existence of NOM did not affect sorption of E2 and EE2 onto cell membranes although their sorption coefficients onto NOM were comparable to those of OP and NP. These phenomena suggested that OP, NP and PAHs bound to NOM could not be sorbed onto cell membranes but E2 and EE2 bound to NOM could; that is, the behavior of E2 and EE2 bound to NOM was similar to the non-bound (free) E2 and EE2.